Characterization by DNA restriction endonuclease analysis of Listeria monocytogenes strains related to the Swiss epidemic of listeriosis. - Nocera, D (1990)
Listeria monocytogenes strains responsible for outbreaks of listeriosis were studied by using serotyping and phage typing. An additional approach based on restriction endonuclease analysis (REA) of the chromosomal DNA was used to characterize L. monocytogenes strains collected from various sources during and after a Swiss outbreak of listeriosis (1983 to 1987). Among the 169 wild-type strains of Listeria spp. that were examined, 161 (95%) belonged to the species L. monocytogenes, of which 109 were of human origin. Ten different REA profiles were obtained from the 120 L. monocytogenes serotype 4b strains tested. All 57 serotype 4b strains that were identified as Swiss epidemic strains by phage typing clustered in two closely related REA profiles. In particular, 10 L. monocytogenes 4b strains isolated from the brand of soft cheese responsible for the outbreak and from its direct environment were indistinguishable from isolates from 40 patients by both phage typing and REA analysis. However, 5 of the 17 non-phage-typeable L. monocytogenes strains and 18 L. monocytogenes strains with a phage type different from those of the Swiss epidemic types showed the same profile. REA enabled the characterization of non-phage-typeable strains and, thus, seems a promising tool for L. monocytogenes typing, especially during epidemiological investigations.